A review Recent Advanced of Fabrication Techniques and Application of Micro-Needle - Borey, Vrushali S.; Ingle, Saurabh. B.; Kotwal, Pooja V.; Jadhao, Amol G.; Sheikh, Taufik R.; Nagrik, Shtrughan U.; Sanap, Jayshri B. (Asian Journal of Pharmaceutical Research and Development, 2023)
Micro-needles are micron-scaled medical devices used to administer vaccines, drugs, and other therapeutic agents. Micro-needles typically measure 0.1–1 mm in length. A variety of materials such as silicon, ceramic, stainless steel and polymers have been used for fabrication. Micro-needles devices are compatible with the delivery of both Small and macromolecular therapeutics. Micro-needles (MNs) are currently being utilized to enhance transdermal delivery of small and large molecules. With the emergence of micro fabrication manufacturing technology over the past several decades, (MNs) have been developed by academic laboratories and pharmaceutical companies. Micro-needle has useful in application in diseases such as type 2 Diabetes, cancer treatment, Glaucoma, and also useful application in cosmetic, vaccine therapy. The present article provides an overview of micro-needle, fabrication technique, general properties, Material and methods of fabrication techniques, application and advantages and disadvantages of micro-needle drug delivery system. Micro-needles (MNs) are currently being utilized to enhance trans-dermal delivery of small and large molecules. With the emergence of micro fabrication manufacturing technology over the past several decades, have been developed by academic laboratories and pharmaceutical companies.